Fibroepithelial Polyp in a Duplicated Ureter - Jae Young Lee; Seung Soo Kim; Chan Ho Park (Journal of the Belgian Society of Radiology, 2020)
Teaching point: A fibroepithelial polyp is an intraluminal, long, slender neoplasm that frequently occurs in the ureteropelvic junction and upper ureter.